Left thoracoscopic approach in the supine position for torsion of the residual esophagus after esophagectomy: a case report - Kazuya Yamaguchi; Shigeo Haruki; Masayoshi Sakano; Kunihito Suzuki; Akinori Miura (Surgical Case Reports, 2022)
Abstract Background Anastomotic stenosis can occur after esophagectomy and gastric tube reconstruction. The effective surgical treatment for refractory anastomotic stenosis, which seems difficult to resolve with endoscopic treatment, has not been established. We report a case of refractory stenosis due to esophageal torsion in which reconstructive surgery was possible using a left thoracoscopic approach in the supine position. Case presentation A 72-year-old man who underwent thoracoscopic subtotal esophagectomy and retrosternal gastric tube reconstruction for esophageal cancer 6 months previously presented to us. Postoperative endoscopy revealed that the residual esophagus was twisted approximately 360°, just above the anastomotic site. Conservative endoscopic treatment failed to improve the condition due to severe passage obstruction, and reconstructive surgery was repeated. Surgery was performed in the supine position using a left thoracoscopic approach. The entire circumferences of the gastric tube and residual esophagus were dissected from the inferior mediastinum to the top of the sternum, with focus on preserving the right gastroepiploic vein and gastric-tube wall. Subsequently, laparoscopic surgery was performed to remove the gastric tube from the thoracoabdominal junction. After separating the esophagus on the oral side of the torsion from the left cervical wound, the abdomen was opened, the gastric tube was pulled out through the abdominal wound, and adhesions in the abdominal cavity were peeled off to raise the gastric tube cranially via the retrosternal route. An end-to-side anastomosis was performed using a circular stapler, and the esophageal torsion and previous anastomosis were resected. Oral intake was resumed on the 7th postoperative day, and the patient was discharged on the 38th day. Conclusions After subtotal esophagectomy and retrosternal gastric tube reconstruction, the left thoracoscopic approach is one of the most minimally invasive approaches and is especially useful for preserving the right gastroepiploic artery and veins and for mobilizing the gastric tube wall.